The Effectiveness of Learning Christian Religious Education with Visual Media Images - Maglon Banamtuan; Kristian E.Y.M Afi; Misael Boineno (Jurnal Pendidikan Agama Kristen (JUPAK), 2022)
The purpose of this study was to describe the level of effectiveness of using visual media images in the learning process of Christian religious education at the Benfomeni Christian Theology High School. The method used in this research is a qualitative research method. The results obtained in the study are: 1). Actively involved students include: students look more focused and happy and not bored in participating in teaching and learning activities in class; 2). Students participate in learning by showing a sense of more interest when Christian religious education teachers use visual media images; 3). The form of the image includes: contextual design aspects; 4). The attractiveness of the visual media is because of the clarity of the image.